Human dimensions of the ecosystem approach to fisheries : - Young, Cassandra De (Food and Agriculture Organization of the United Nations, 2008)
This document aims to provide a better understanding of the role of the economic, institutional and sociocultural components within the escosytem approach to fisheries (EAF) process and to examine some potentials methods and approaches that may facilitate the adoption of EAF management.